High VEGFR1/2 expression levels are predictors of poor survival in patients with cervical cancer. Issue 1 (January 2017) - Dang, Yun-Zhi; Zhang, Ying; Li, Jian-Ping; Hu, Jing; Li, Wei-Wei; Li, Pei; Wei, Li-Chun; Shi, Mei
Abstract : Abstract: The aim of the study to evaluate the prognostic significance of vascular endothelial growth factor receptor 1 and 2 (VEGFR1/2) expression levels and to correlate these levels with clinicopathological parameters in patients with cervical cancer. Forty-two patients with International Federation of Gynecology and Obstetrics Stage IIB–IVB cervical cancer were analyzed between January 2011 and December 2012. RNA expression levels of VEGFR1/2 were assessed by branched DNA-liquidchip technology and immunohistochemistry. Associations between RNA expression levels, important clinicopathological parameters, and patient survival were statistically evaluated. Higher VEGFR1/2 expression levels were predictive of poor overall survival ( P  = 0.009 and P  = 0.024, respectively). Patients with higher VEGFR1 expression levels were associated with poorer progression-free survival than those with lower VEGFR1 expression levels ( P  = 0.043). In addition, patients with higher VEGFR1 expression levels were more likely to develop distant metastases than those with lower VEGFR1 expression levels ( P  = 0.049). Higher VEGFR2 expression levels were associated with larger tumor size ( P  = 0.037). VEGFR1/2 expression levels were prognostic factors for patients with cervical cancer. Higher VEGFR1/2 expression levels were also predictive of poor overall survival. Abstract : Supplemental Digital Content is available in the text